Targeting Head and Neck Cancer by Vaccination - Wang, Chuan; Dickie, James; Sutavani, Ruhcha V.; Pointer, Catherine; Thomas, Gareth J.; Savelyeva, Natalia (Frontiers in Immunology, 2018)
Head and Neck cancer (HNC) is a heterogeneous group of squamous cell cancers that affect the oral cavity, pharynx and larynx. Worldwide it is the 6th most common cancer but in parts of Southern and South-East Asia, HNC is one of the most common cancers. A significant proportion of HNC is driven by human papillomavirus (HPV) infection whereas HPV-independent HNC is associated with alcohol, smoking and smokeless tobacco consumption. Here we review the past and present experience of targeting HNC with vaccination focusing on HPV derived antigens as well as non-viral antigens for HPV-negative HNC. Novel therapeutic approaches for HNC will focus not only on effective vaccine platforms but will also target the stroma-rich immunosuppressive microenvironment found in those tumours.